1989
DOI: 10.3382/ps.0680017
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Versus Susceptibility to Marek’s Disease

Abstract: It was hypothesized that the generation of activated T cells through an efficient and rapid immune response during the early pathogenesis of Marek's disease virus (MDV) infection provides a large pool of target cells for transformation. Therefore, the correlation between genetic susceptibility to Marek's disease (MD) and in vitro mitogenic responses of lymphocytes as a measure of cell-mediated immune competence and efficiency was tested. In one series of trials, spleen cells from strains of chickens with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In addition most of the correlations between PHA response and MD resistance were non significant (table V). Therefore, in agreement with Calnek et al (1989), who studied in vitro PHA response of lymphocytes from strains of varying resistance to MD, we conclude that swelling response to PHA inoculation in the wing web is not sufficiently predictive of MD resistance to justify its use in genetic selection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition most of the correlations between PHA response and MD resistance were non significant (table V). Therefore, in agreement with Calnek et al (1989), who studied in vitro PHA response of lymphocytes from strains of varying resistance to MD, we conclude that swelling response to PHA inoculation in the wing web is not sufficiently predictive of MD resistance to justify its use in genetic selection.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, Lee and Bacon (1983) reported that increased in vitro response of lymphocytes to phytohemaglutinin was associated with increased susceptibility to MD. However, Calnek et al (1989) dit not observe any general correlation between the responses of multiple genetic groups of chickens to mitogens Concavalin A and PHA or mixed lymphocyte reaction, and MD susceptibility.…”
Section: Introductionmentioning
confidence: 65%
“…Many studies provide data showing greater immune responsiveness in MHC-B genetically susceptible birds. For example, lymphocytes from MDsusceptible Line P (MHC-B19) are more responsive to mitogens (ConA and PHA) than birds from MHC-B-resistant Line N birds (MHC-B21) (29,30). When infected in vitro lymphocytes from MHC-B-susceptible lines produce significantly more infected T cells compared to lymphocytes from MHC-B-resistant lines (31).…”
Section: Discussionmentioning
confidence: 99%
“…These points lend credence to the theory (Cohen et al, 1985) that a low immune response may, in some instances, be beneficial to disease resistance, rather than being detrimental. With reference to Marek's disease, it is possible that a decreased cell-mediated immune (CMI) response may be associated with improved resistance to viral transformation, as has been suggested by Calnek et al (1989). Although their results did not show the hypothesized association for all lines tested, several reasons for this discrepancy were given.…”
Section: Discussionmentioning
confidence: 55%